Photoacoustic molecular imaging with functional nanoparticles - Liming Liu (Journal of Innovative Optical Health Sciences, 2017)
Photoacoustic imaging (PAI) breaks through the optical diffusion limit by making use of the PA effect. By converting incident photons into ultrasonic waves, PAI combines high contrast of optical imaging and high spatial resolution in depth tissue of ultrasound imaging in a single imaging modality. This imaging modality has now shown potential for molecular imaging, which enables visualization of biological processes with systemically introduced functional nanoparticles. In the current review, the potentials of different optical nanoprobes as PAI contrast agents were elucidated and discussed.